Camp out - LaReau, Kara (LaReau, Kara. Infamous Ratsos, 2020)
Louie and Ralphie Ratso and the rest of the Big City Scouts are going camping for the first time. And they have a special guide: Grandpa Ratso! Grandpa teaches everyone the Scouts oath, which says Scouts are always able to solve problems without asking for help. But the Scouts soon discover that figuring out how to pitch a tent, make a fire, and find their way is tough to do by themselves. In fact, not asking for help isn't working at all, and everybody is hungry, tired, lost, and itchy! Luckily, someone unexpected sets things straight about what the oath really says - and it isn't about doing things on your own!--publisher's description.